IMPACT OF THE USE OF THE SPEECH VALVE ON THE SWALLOWING AND DECANULATION PROCESS - Regina Nantes de Oliveira, Karla; Galdino Franco, Patrícia; Cristina Ribeiro Akamine, Suellen (Health and Society, 2021)
The speech valve can be safe and effective for tracheostomized, conscious patients with tolerance to deflated cuff. It can be coupled between 48 and 72 hours after tracheostomy, depending on the airway permeability. Objective: The objective of this study was to identify the impact of the use of the speech valve on adult patients hospitalized in the city of Campo Grande, in the state of Mato Grosso do Sul, aiming at swallowing, reintroduction of diet orally in a safe way and decannulation. Method: The longitudinal method with indirect and direct evaluation with PAP, PITA, PARD, BLUE DAY TEST, DECANULATION PROTOCOL AND SCALE was used in adult and hospitalized patients. Results: Regarding the criterion of time for decannulation, after the beginning of the training with the speech valve, we consider the following findings. All patients decannulated within a maximum of 15 days after the use of the speech valve. All started oral feeding in a maximum of 7 days after using the speech valve. And SNE was removed in all patients within 15 days after using the speech valve. There is evidence that the use of the speech valve has positive impacts on the swallowing process, reintroduction of the diet orally in a safe way and on the decannulation process. Conclusion: It was concluded that the use of the speech valve brought benefits to patients, in addition to facilitating the phonation process and the adjustment of the respiratory pattern closer to the physiological one before decannulation has an importance in swallowing and a decrease in the time of swallowing. Decannulation.